MASALAH DALAM PENGELOLAAN KOTA LAMA SEMARANG SEBAGAI NOMINASI SITUS WARISAN DUNIA - Ardiana Yuli Puspitasari; Wa Ode Sitti Khasana Ramli (Universitas Islam Sultan Agung Semarang, 2018)
World Heritage Sites is a term addressed to special places such as national parks, forests, mountains, lakes, deserts, buildings, complexes, regions, rural and cities that have been nominated by UNESCO (United Nations Educational, Sciencetific, and Cultural Organization) for the International World Heritage program. The Old City of Semarang in 2016 has entered as one of the nominees of World Heritage Site and until now is in the process of submitting terms to become World Heritage Site. One of the important things that need to be done in the process is to identify and inventory the problems to be handled immediately. The purpose of this research is to find the problems in the management of the Old City of Semarang so that it can be handled and anticipated. The research method used is qualitative rationalistic with empirical approach. The results of this research are the problems that occur in the Old Town of Semarang is quite complex and diverse, among others: 1) environmental problems, namely prone to natural disasters (rob floods and puddles), high traffic volume causes pollution of fading and vibration , the unavailability of public transportation